Antibacterial activities of biocomposite plastic-based phenolic acids-grafted chitosan and sugar palm starch (Arenga pinata). Issue 1 (March 2020) - Anwar, M; Istiqomah, L; Ekaningrum, M; Yembise, D
Abstract: Antibacterial activity of biocomposite plastics based sugar palm starch (SPS) and phenolic acid-grafted chitosan has been investigated. The various type of active compounds (ferulic acid-grafted chitosan, caffeic acid-grafted chitosan, and coumaric acid-grafted chitosan) was synthesis by free radical method and was evaluated by using FTIR and calculate the degree of substitution by using Folin-Ciocalteu procedure. The biocomposite plastics were made by combined SPS with glycerol, cellulose, zeolite, and active compounds (phenolic acid-grafted chitosan). Morphological structures were analyzed by using SEM, and antibacterial activities were evaluated by using agar diffusion method. It was found that the grafting reaction of phenolic acids was not improved the antibacterial activities. The biocomposite plastics impregnated with grafted products were showed no clear zone.